Preparation and antibacterial activity of solvothermal synthesized ZnFe2O4/Ag-TiO2 nanocomposite - Soner Çakar; Keziban Atacan; Nuray Güy (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this study, ZnFe2O4magnetic nanoparticlesandZnFe2O4/Ag-TiO2nanocomposite were synthesized solvothermally. The preparedmaterials were characterized using X-ray diffraction, Scanning electronmicroscopy, Fourier transform infrared spectroscopy and Vibrating samplemagnetometer. In addition, the antibacterial performance of materials wasevaluated against Gram-positivebacteria (Staphyloccocus aureus) and Gram-negativebacteria (Escherichia coli). ZnFe2O4/Ag-TiO2 nanocomposite was shown strongerantibacterial efficiency against Gram-positive bacteria Staphyloccocus aureus than Escherichiacoli. Also, the inhibition diameter of 15±0.2 mm for ZnFe2O4/Ag-TiO2 nanocomposite wasmeasured since the antibacterial activity increased by nanocomposite formation.